2020
DOI: 10.3390/ijms21031106
|View full text |Cite
|
Sign up to set email alerts
|

STAT3/5 Inhibitors Suppress Proliferation in Bladder Cancer and Enhance Oncolytic Adenovirus Therapy

Abstract: The JAK-STAT signalling pathway regulates cellular processes like cell division, cell death and immune regulation. Dysregulation has been identified in solid tumours and STAT3 activation is a marker for poor outcome. The aim of this study was to explore potential therapeutic strategies by targeting this pathway in bladder cancer (BC). High STAT3 expression was detected in 51.3% from 149 patient specimens with invasive bladder cancer by immunohistochemistry. Protein expression of JAK, STAT and downstream target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 67 publications
(95 reference statements)
2
44
0
Order By: Relevance
“…Consistent with the literature, our results found that shBCL2L15 EEC proliferation was inhibited by fludarabine treatment. However, Stattic induced significant apoptosis at 24 h in shBCL2L15; these results reflect those of Sruthi et al, who also found that Stattic induced bladder cancer cell apoptosis at 24 h by arresting the G2/M cell cycle [44]. Blocking the STAT1 pathway with fludarabine increased the expression of genes promoting conceptus elongation, endometrial receptivity markers, cell adhesion molecules, and PGR, except for ITGB3.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the literature, our results found that shBCL2L15 EEC proliferation was inhibited by fludarabine treatment. However, Stattic induced significant apoptosis at 24 h in shBCL2L15; these results reflect those of Sruthi et al, who also found that Stattic induced bladder cancer cell apoptosis at 24 h by arresting the G2/M cell cycle [44]. Blocking the STAT1 pathway with fludarabine increased the expression of genes promoting conceptus elongation, endometrial receptivity markers, cell adhesion molecules, and PGR, except for ITGB3.…”
Section: Discussionsupporting
confidence: 83%
“…To investigate how PRDX6 regulated cell proliferation signaling, the GSEA analysis and found JAK-STAT3 pathway was significantly enriched in PRDX high group (Figure 6E, Figure 8A). STAT3 plays as an important role in urological related tumors 34 , and previous study has confirmed that STAT3 as the upstream signaling of CDK4/6 pathway 35 . Taken together, we speculated that JAK-STAT3 signaling can be regulated by PRDX6 to impact the proliferation of BLCA cells.…”
Section: Prdx6 Promotes Bladder Cancer Cell Proliferation Via Jak2-stmentioning
confidence: 79%
“…IFN-I activates the protein kinase RNA-activated (PKR) signaling pathway leading to protein synthesis blockade and viral clearance [ 98 ]. Tumor cells have defects in antiviral pathways such as IFN-I, PKR, and JAK-STAT, resulting in the survival and proliferation of OVs, specifically in tumor cells [ 99 , 100 , 101 ]. Lysis of OV-infected cells releases a very diverse TAAs that prime immune cells to induce a local and systemic vaccination against the released TAAs [ 92 ].…”
Section: Oncolytic Virus Effects On Tmementioning
confidence: 99%